New Paradigm of Employee Productivity - Cahyati, Peni; Kartilah, Tetet; Mulyatini, Nurdiana (International Journal of Advanced Multidisciplinary, 2023)
The purpose of this study was to assess the extent to which the implementation of current education and training programs affects the job productivity of kindhearted employees. According to the findings from data analysis, there are certain factors pertaining to the execution of education and training programs that should be taken into account and improved upon. These factors include: In order to enhance the efficiency of employees, there are several key elements that must be considered when implementing instructional and training programs. These include the preparation of materials, non-formal instruction, plan preparation, fostering camaraderie among educators, offering diverse training options, implementing effective strategies, and creating comprehensive training manuals. Additionally, it is crucial to maintain formal instruction, ensure teachers possess the necessary skills and capacities, provide adequate training facilities, develop comprehensive training curricula, and conduct regular assessments. The successful implementation of these instructional and training programs directly impacts the productivity of employees. Despite the theoretical nature of training programs, their practical application remains significant in the work of employees. Therefore, an appropriate and well-designed instructional and training program will undoubtedly contribute to increased employee productivity.